2015
DOI: 10.1515/geo-2015-0047
|View full text |Cite
|
Sign up to set email alerts
|

Response of lateral channel dynamics of a lowland meanderingriver to engineering-derived adjustments - an example of theMorava River (Czech Republic)

Abstract: Freely meandering (quasi)natural reaches of lowland rivers represent a rare phenomenon in Central Europe. Increasing attention is currently being paid to the dynamics of quasi-natural (arti cially in uenced) meandering rivers as this attention represents the basic prerequisite for the development of appropriate restoration strategies on regulated rivers. This study focused on a 5.5 km long reach of the Morava River in the Strážnické Pomoraví region, Czech Republic that is characterised by quasi-natural evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Our results have shown some similarities with other European rivers. Ondruch and Máčka (2015), who worked on the Morava River (Czech Republic), found that the correlation between the duration of discharges was equal or higher than the effective discharge and the bank erosion rates, reaching 0.57. However, they investigated only a 5.5 km long reach and the meandering reaches showed a correlation of only 0.26, while along the Sajó River, it was 0.59, 0.61 and 0.59 regarding the total reach, the natural and the artificial reaches, respectively (Suppl.…”
Section: Discussionmentioning
confidence: 98%
“…Our results have shown some similarities with other European rivers. Ondruch and Máčka (2015), who worked on the Morava River (Czech Republic), found that the correlation between the duration of discharges was equal or higher than the effective discharge and the bank erosion rates, reaching 0.57. However, they investigated only a 5.5 km long reach and the meandering reaches showed a correlation of only 0.26, while along the Sajó River, it was 0.59, 0.61 and 0.59 regarding the total reach, the natural and the artificial reaches, respectively (Suppl.…”
Section: Discussionmentioning
confidence: 98%
“…Morphological changes allow registering high rates of bank erosion, which in similar investigations in other European rivers, was also calculated [3,73,74]; however, the extent of arable lands lost by lateral erosion is not an outstanding value compared to other rivers with similar geomorphological patterns [75]. In this way, it would be a great opportunity to include in future investigations the correlation between these morphological alterations, the changes in the biodiversity and the bank erosion rates.…”
Section: Discussionmentioning
confidence: 83%